Pathway-specific inhibition of primaquine metabolism by chloroquine/quinine. (December 2016) - Fasinu, Pius; Tekwani, Babu; Avula, Bharathi; Chaurasiya, Narayan; Nanayakkara, N.; Wang, Yan-Hong; Khan, Ikhlas; Walker, Larry
Abstract Background There has been some evidence to suggest that the addition of chloroquine (CQ) or quinine (QN) to 8-aminoquinoline (8-AQ) treatment regimens may increase the therapeutic efficacy of the 8-AQ and simultaneously mitigate against its haemolytic toxicity. However, both CQ and QN are considered effective, although perhaps moderate inhibitors of CYP2D6, an enzyme now regarded as necessary for primaquine (PQ) pharmacologic activity. An understanding of the influence of CQ and QN on the metabolism of PQ may shed light on the potential mechanisms of the beneficial interaction. Methods Differential metabolism of PQ enantiomers by recombinant human CYP2D6, monoamine oxidase A (MAO), and cryopreserved human hepatocytes in the presence/absence of CQ and QN. Results Both CQ and QN significantly inhibited the activity of CYP2D6. PQ depletion by MAO and human hepatocytes was not affected significantly by the presence of CQ and QN. CYP2D6-mediated hydroxylation was largely suppressed by both CQ and QN. The formation of the primary deaminated metabolites, including carboxyprimaquine (CPQ) and cyclized side chain derivative from the aldehyde (m/z 241), was not sensitive to the presence of CQ and QN. However, the appearance of the glucuronides of CPQ and PQ alcohol were significantly suppressed. CQ and QN also inhibited the appearance of them/z 257 metabolite with a similar pattern, suggesting that it may be derived from the CPQ conjugate. The apparent quinone-imine of CPQ (m/z 289) was only partially suppressed by both QN and CQ, but with a differential pattern of inhibition for the two drugs. Them/z 274 (quinone-imine of a ring-hydroxylated PQ metabolite) andm/z 422 (an apparent glucose conjugate of PQ) metabolites in hepatocytes were strongly suppressed by both QN and CQ, perhaps a reflection of the 2D6 inhibition by these drugs. The formation of the carbamoyl glucuronide of PQ (m/z 480) was not affected by CQ/QN. Conclusion The metabolite-specific interactions in the current studies seem at variance with earlier reports of the dependence of PQ on CYP2D6 metabolism, and enhanced PQ anti-malarial activity/reduced toxicity in the presence of CQ/QN. These results suggest a complex picture in which CQ/QN may shift metabolite pathway balances towards a profile that retains efficacy, while reducing the formation or availability of toxic metabolites to erythrocytes. Alternatively, these drugs may alter transport or distribution of PQ metabolites in a fashion that reduces toxicity while maintaining efficacy against the parasite.